Postchemotherapy residual masses in advanced seminoma: current management and outcomes. Issue 5 (October 2005) - Quek, Marcus L; Simma-Chiang, Vannita; Stein, John P; Pinski, Jacek; Quinn, David I; Skinner, Donald G
Although pure testicular seminoma is most often confined to the testis, it can present with advanced-stage bulky retroperitoneal metastases in nearly a quarter of cases. While highly treatable with cisplatin-based chemotherapy, up to 80% of patients with advanced disease are found to have a radiographically detectable residual mass after chemotherapy. The management of these postchemotherapy residual masses remains controversial. Surgical resection is technically challenging due to a desmoplastic reaction resulting from seminoma treatment and regression. In addition, these residual masses often demonstrate a protracted period of regression that can span several months to years. Surveillance protocols, therefore, may be appropriate for most patients. Several retrospective studies have supported surgical resection only for discrete, well-delineated masses over 3 cm in size. Despite the highly radiosensitive nature of seminoma, radiation therapy in this setting has not been shown to provide significant benefit, and may limit the tolerability of subsequent salvage chemotherapy. The incorporation of noninvasive imaging modalities, such as positron emission tomography, into the management algorithm may better delineate the presence of viable residual tumor and thus allow better risk stratification.